2020
DOI: 10.25208/vdv1188-2020-96-5-24-30
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of phototherapy in patients with mycosis fungoides: preliminary results of a comparative non-randomized study

Abstract: Clinical reasoning. There is a need to optimize the use of UV-B-311 nm and PUVA-therapy in patients with mycosis fungoides to determine the duration of the treatment regimen, the number of sessions per week, and ultraviolet irradiation regimen. Goal of research. Evaluation of the effect of the type and duration phototherapy on efficacy in patients with mycosis fungoides. Principle. A comparative, non-randomized study of the effectiveness of phototherapy in patients with mycosis fungoides in the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In that way, the cytokine environment substantially determines the prognosis of the disease by affecting the phenotype and functional properties of skin T-lymphocytes [9]. e early stages of cutaneous T-cell lymphoma (MF) can be managed with skin-targeted therapy [10,11]. Recent studies have demonstrated the high efficacy of NB-UVB and PUVA in MF [12].…”
Section: Introductionmentioning
confidence: 99%
“…In that way, the cytokine environment substantially determines the prognosis of the disease by affecting the phenotype and functional properties of skin T-lymphocytes [9]. e early stages of cutaneous T-cell lymphoma (MF) can be managed with skin-targeted therapy [10,11]. Recent studies have demonstrated the high efficacy of NB-UVB and PUVA in MF [12].…”
Section: Introductionmentioning
confidence: 99%